Procalcitonin levels in severe fever with thrombocytopenia syndrome patients: a retrospective investigation in Anhui, China - Wang, Wenjie; Yang, Yang; Liang, Manman; Zhang, Aiping; Zhang, Zhaoru; Yang, Jianghua (The Journal of Infection in Developing Countries, 2024)
Introduction: This work aim to evaluate the association of procalcitonin (PCT) levels with disease severity and prognosis in severe fever with thrombocytopenia syndrome (SFTS) patients. Methodology: The medical records of 158 confirmed SFTS patients at two hospitals were reviewed. The patients were divided into survival group and nonsurvival group according to outcomes. Additionally, to assess mortality rates at different PCT levels, patients were divided into two groups, PCT < 0.25 ng/mL and PCT ≥ 0.25 ng/mL. Results: Among the 158 confirmed SFTS patients, 26 died; the case fatality rate was 16.46%. PCT data were available for 132 of these patients; 66 were in the PCT < 0.25 ng/mL group, and 66 were in the PCT ≥ 0.25 ng/mL group. The SFTS patients had abnormal results on routine blood tests, indicating varying degrees of thrombocytopenia and leukopenia, and most patients presented with multiple organ dysfunction. The PCT level of the nonsurvival group was significantly higher than that of the survival group (p < 0.01). Additionally, the mortality of the PCT ≥ 0.25 ng/mL group was significantly higher than that of the PCT < 0.25 ng/mL group (p < 0.01); mortality increased sharply ( ≥ 25%) when the PCT level exceeded 0.1 ng/mL. Conclusions: PCT levels in SFTS patients are closely related to the severity and prognosis of their illness. The serum PCT level is a promising predictor of mortality and severity in SFTS patients when considered in combination with clinical data and other laboratory tests.